ASPECTOS DO PROCESSO DE SÍNTESE DA CERÂMICA DO TITANATO DE COBRE E CÁLCIO OBTIDA PELO MÉTODO SOL-GEL - Alves, Vinícius; Gonçalves, Rony; Aparecido, Rafael; Stropa, Jusinei; Vieira, Graciele; Cavalheiro, Alberto (ANAIS DO ENIC, 2018)
-